Clinical aspects of the treatment of Charcot osteoarthropathy - Гладких, Ф.В.; Балатюк, І.А.; Яворський, О.М.; Сокирко, М.В. (Abstracts of the ІХ-th International Interdisciplinary Scientific Conference of Young Scientists and medical students «Actual problems of clinical and theoretical medicine» (International Scientific Interdisciplinary Conference – ISIC: abstracts (May 19–20, 2016). Kharkiv, 2016. P. 314–315., 2016)
Clinical aspects of the treatment of Charcot osteoarthropathy.
Balatiuk I. A., Hladkykh F. V., Yavorskyi O. M., Sokyrko M. V. Clinical aspects of the treatment of Charcot osteoarthropathy. Abstracts of the ІХ-th International Interdisciplinary Scientific Conference of Young Scientists and medical students «Actual problems of clinical and theoretical medicine» (International Scientific Interdisciplinary Conference – ISIC: abstracts (May 19–20, 2016). Kharkiv, 2016. P. 314–315.
Keywords: Charcot osteoarthropathy; osteoarthropathy